DEVELOPING INTERNATIONAL STUDIES AT VNU-ULIS IN THE CONTEXT OF GLOBALIZATION: IDENTITY WITHIN DIVERSITY - Ha Thanh, Phung; Thanh Ha, Nguyen; Thi Minh Tam, Nguyen; Thi Hanh, Hoang; Dieu Hong, Nguyen; Thi Thanh Hoa, Hoang (VNU Journal of Foreign Studies, 2021)
This article outlines the development and contemporary features of international studies in the world and in Vietnam. Against that background, it describes the unique case of advancing international studies in the direction of transnational media and cultural studies at Faculty of Linguistics and Cultures of English-speaking Countries, VNU University of Languages and International Studies (VNU-ULIS). All in all, the article highlights the transnational turn, interdisciplinarity, and the variegated and changing nature of contemporary social sciences and humanities. This new situation demands rethinking the academic structure of Vietnam’s higher education for better flexibility and sustainability grounded in particular, organic strengths of academic institutions. Recommendations for developing international studies at VNU-ULIS are also offered.